EFFORTS TO DEVELOP CHILDREN FINE MOTOR SKILLS THROUGH STICKING PICTURE PROPERLY BY USING COMBINATION OF EXPLICIT INSTRUCTION MODEL AND ASSIGNMENT MEDIA UTILIZING NATURAL MATERIALS - Metroyadi, Metroyadi; Mardhiah, Amalia (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
The objective of the research is to develop children fine motor skills through sticking picture properly by using combination of explicit instruction model and assignment media utilizing natural materials. This research is classroom action research conducted in two cycles of three meetings at Kenanga Kindergarten of Gambut District, Banjar Regency, academic year of 2016/2017 with involving 20 children, consisted of 13 males and 7 females. Data collected through observation sheet activities of teachers, children, and the achievement of children fine motor development during the learning. The research results showed that the learning activities performed by teachers was suitable to the planning and students? activities in very active and the achievement of student is 95% classically. It is recommended to other Kindergarten teachers in the effort to develop fine motor skills through sticking picture properly to use the combination of explicit instruction model and assignment method utilizing natural materials media.